HUBUNGAN PENGETAHUAN IBU DENGAN SIKAP DALAM PEMENUHAN NUTRISI PADA BALITA (0-5 TAHUN) DI DUSUN REJO SARI DESA KWALA BEGUMIT KECAMATAN STABAT KABUPATEN LANGKAT TAHUN 2012 - Sarida Surya Manurung (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2019)
Malnutrition can be prevented by knowing the causes and precipitating factors, then the mother would be easier to accept and be able to recognize themselves beyond what factors can trigger. This study aimed to see whether there is knowledge Relationship Mother With Attitude In Nutrition Fulfillment In Toddlers (0-5 years). This study is a cross-sectional design Analytical conducted in Hamlet Rejo Sari Village Kwala Begumit Stabat District of Langkat from April to May 2012. The number of samples is 48 mothers of the total population of 73 families in the village Rejo Sari. Data collected by using a questionnaire filling. Analysis of data using statistical test Chi - Square analysis and analyzed using SPSS (Statistics System Processing Standard) obtained results mean p = 0.001 p <0.05. The results of this study indicate that there is a relationship between mother with Attitude Knowledge Fulfillment particularly in nutrition. The results of this study, the majority have sufficient knowledge of 25 respondents (52.1%) and have enough attitude as much as 20 respondents (41.7%), bad attitude by 4 respondents (8.3%), good knowledge of as many as 17 respondents (35 , 4%) and have a good attitude as much as 24 respondents (50.0%), attitude pretty much as 20 respondents (41.7%), and who have poor knowledge as much as two respondents (33.3%) and have enough attitude as much as 14 respondents (56.0%), bad attitude as much as two respondents (33.3%).